Development of an enzyme-linked immunosorbent assay for determining FSH plasma concentrations in green sea turtle (Chelonia mydas), using recombinant gonadotropins - Soffer, Osher; Rubin, Olga; Levy, Yaniv; Aizen, Joseph (Frontiers in Marine Science, 2023)
Follicle-stimulating hormone (FSH) is involved in the regulation of essential reproductive processes such as gametogenesis and follicular growth. There are presently no immunoassays for measuring FSH in turtles. Recently we produced green sea turtle (Chelonia mydas) recombinant (r) FSH as a single-chain polypeptide using the methylotrophic yeast Pichia pastoris expression system, and polyclonal antibodies for the recombinant FSH. In this work we developed a competitive enzyme-linked immunosorbent assay (ELISA) for the measurement of FSH concentrations in plasma samples from green sea turtles. We used the rFSHβα for standard, rFSHβ for coating and a cmFSHβ antibody. The sensitivity of the assay was 0.13 ng/ml and the intra-assay and inter-assay coefficients of variation were 5.54% and 13.52% respectively. Parallelism was observed between the linearized FSH standard curves and the corresponding serial dilutions of green sea turtle plasma samples. We also observed parallelism between the linearized standard and serial dilutions of plasma samples from the loggerhead sea turtle (Caretta caretta), hawksbill sea turtle (Eretmochelys imbricate), and African softshell turtle (Trionyx triunguis). The ELISA was used to study the FSH plasma concentrations during the reproductive cycles and was compared to hormonal steroid concentrations (Testosterone, Estradiol and Progesterone). This revealed a positive correlation between FSH and estradiol concentrations in females; estradiol concentrations were increased immediately after FSH elevation. In addition, nested females presented an increase in FSH concentrations prior to progesterone elevation in January to April, slightly before egg laying. This ELISA will increase our understanding of gonadotropin functions, and their effects on reproduction in the green sea turtle.